Implications and future strategies on cost management for hospitals during and after COVID-19 - Raghuvanshi, Vijay Pratap; Raghuvanshi, Shiv Pratap (International Journal Of Community Medicine And Public Health, 2020)
The coronavirus disease (COVID-19) pandemic is throwing a new factor into hospitals calculations about how to proceed with current and future healthcare strategy implementations. As entire nations encourage their populations to remain stay home, quarantine, avoid coming out and wear masks till lockdown open, while healthcare providers doctors, nurses, technicians and other administrative staffs are more active than ever in response to the outbreak of the novel coronavirus. We expect a significant increase in costs after the pandemic due to change in services and infrastructure, use of personal protective equipment and extra sanitization used by medical staff. To identify ways to improve liquidity, cash flow and cost management due to damage done by COVID -19, we systematically reviewed journals on cost management in hospitals, reports from healthcare finance management agencies, conducted focus groups webinar and websites that includes health policies, healthcare management costs, finance and factors such as departmental cost management in hospitals. The results were clubbed into two parts i.e. one was healthcare revenue challenge and second was strategies for regenerate revenue during and after COVID-19. COVID-19 has shown a significant impact on the healthcare revenue cycle, financial operations, supply chain management, hospital operations and even for those who provide finances. Hospitals and healthcare systems needs to do the work on war footing in supply chain, clinical services, diagnostics services and operations management by ensuring that the management drives the strategies, transform process, create cost-reduction goals and identify possible sources of savings based on the organizations capital and liquid shortfall, using internal and external benchmarking.